2020
DOI: 10.3390/nu12103159
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Fish Oil Supplementation: The Effects of Alternative Plant Sources of Omega-3 Polyunsaturated Fatty Acids upon Lipid Indexes and Cardiometabolic Biomarkers—An Overview

Abstract: Cardiovascular diseases remain a global challenge, and lipid-associated biomarkers can predict cardiovascular events. Extensive research on cardiovascular benefits of omega-3 polyunsaturated fatty acids (n3-PUFAs) is geared towards fish oil supplementation and fish-rich diets. Nevertheless, vegetarianism and veganism are becoming more popular across all segments of society, due to reasons as varied as personal, ethical and religious values, individual preferences and environment-related principles, amongst oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 112 publications
(142 reference statements)
0
37
0
4
Order By: Relevance
“…Another small crossover Japanese trial recently reported enhanced fat oxidation in healthy subjects, administered with 2.5 g/d of ALA-enriched diacylglycerol vs. placebo [ 133 ], suggesting its use in visceral obesity prevention. Other evidence indicative of the cardioprotective effects of ALA come from epidemiological data linking high consumption of ALA-rich foods, such as walnuts [ 134 , 135 ], flaxseed [ 136 ], and some seed oils [ 137 ]. Currently, large-scale primary or secondary prevention trials are missing, and, in summary, the cardiovascular actions of ALA have been poorly explored and remain to be fully elucidated [ 109 ].…”
Section: Dietary Fats: Why We Need Them?mentioning
confidence: 99%
“…Another small crossover Japanese trial recently reported enhanced fat oxidation in healthy subjects, administered with 2.5 g/d of ALA-enriched diacylglycerol vs. placebo [ 133 ], suggesting its use in visceral obesity prevention. Other evidence indicative of the cardioprotective effects of ALA come from epidemiological data linking high consumption of ALA-rich foods, such as walnuts [ 134 , 135 ], flaxseed [ 136 ], and some seed oils [ 137 ]. Currently, large-scale primary or secondary prevention trials are missing, and, in summary, the cardiovascular actions of ALA have been poorly explored and remain to be fully elucidated [ 109 ].…”
Section: Dietary Fats: Why We Need Them?mentioning
confidence: 99%
“…Nutritional intervention for women with polycystic ovary syndrome has attracted attention. In recent years, studies have shown that dietary fat is currently considered as a biological regulator affecting metabolism, and ω-Polyunsaturated fatty acids (n-3PUFA) may be the most effective metabolic fatty acid regulator (12)(13)(14)(15). Animal studies shown that n-3 PUFAs can prevent IR by activating PPARa, reducing inflammation, and depositing fat in insulin-sensitive tissues (16).…”
Section: Introductionmentioning
confidence: 99%
“…Omega-3 fatty acids may be the most effective fatty acid regulators in metabolic function, which also have beneficial effects on the risk of cardiovascular disease (5,6). Previous studies have indicated that therapy with omega-3 fatty acids positively impact cardiometabolic and lipid profiles (7) and induced IR (8). Meanwhile, animal studies have also found that omega-3 fatty acid supplementation can improve IR via activating peroxisome proliferatoractivated receptor alpha (PPARa), decreasing inflammation and fat accumulation in insulin sensitive tissues (9).…”
Section: Introductionmentioning
confidence: 99%